Getting started in research: designing and preparing to conduct a research study. (February 2015) - Macfarlane, Matthew D; Kisely, Steve; Loi, Samantha; Macfarlane, Stephen; Merry, Sally; Parker, Stephen; Power, Brian; Siskind, Dan; Smith, Geoff; Looi, Jeffrey C
Objective: To discuss common pitfalls and useful tips in designing a quantitative research study, the importance and process of ethical approval, and consideration of funding. Conclusions: Through careful planning, based on formulation of a research question, early career researchers can design and conduct quantitative research projects within the framework of the Scholarly Project or in their own independent projects.